Improved stability and controlled release of CLA with spray-dried microcapsules of OSA-modified starch and xanthan gum. (20th August 2016) - He, Huizi; Hong, Yan; Gu, Zhengbiao; Liu, Guodong; Cheng, Li; Li, Zhaofeng
Highlights: A proven design for the encapsulation and controlled release of bioactive molecules. Spray-dried microcapsules protected conjugated linoleic acid from oxidation. Microcapsules were susceptible to pancreatic degradation, not to gastric digestion. Abstract: The objective of this investigation was to improve the stability of CLA and to allow for its controlled release by encapsulating it with combinations of octenyl-succinic anhydride (OSA) starch and xanthan gum (XG) in three ratios (OSA/XG: 60/1, 80/1, and 100/1, w/w). The wall material was examined using FTIR and TGA. The microcapsules were characterized by laser particle size analysis (LPS) and SEM. Oxidation of the microcapsules was monitored by headspace method. The results revealed that microcapsules created with an OSA/XG ratio of 60/1 provided superior protection to CLA against oxidation. When CLA-microcapsules were subjected to conditions simulating those in the human gastrointestinal system, 12.1%–50.1% of the CLA was released. CLA encapsulation in spray-dried microcapsules of OSA/XG appears to be an effective technique that provides good protection against oxidation and could be useful in the targeted delivery of functional lipids or other bioactive components to the small intestine.